Landscape spatial analysis as a base for dendrochronological sampling: The case of the Biosphere Reserve of Monarch Butterfly, Mexico - Carlón-Allende, Teodoro; Mendoza, Manuel E.; Villanueva-Díaz, José; Pérez-Salicrup, Diego R. (Instituto de Ecología, A.C., 2016)
Landscape spatial analyses using Remote Sensing (RS) and Geographic Information Systems (GIS) has been scarcely used to indentify sites with dendrochronological potential. For this study, we designed a protocol to identify areas with climatically sensitive trees, based on the spatial analysis of landscape biophysical features. The protocol included the analyses of slope angles, slope aspect, and the distribution of Land Cover and Land Use (LCLU) using RS and GIS tools. The protocol was validated through dendrochronological sampling in two adjacent sites. Analyses of tree ring widths were done using COFECHA and dplR. Results suggest that sensitive trees grow in 18% of the Monarch Butterfly Biosphere Reserve. Trees from the two sites differed in age, diameter, and mean ring width. Our protocol allowed us to identify sites with long-lived and sensitive trees as represented by the high inter-annual variation found in tree ring widths. The spatial analysis of biophysical variables prior to sampling enables the identification of sites with sensitive trees implying the elimination of less samples. Our proposed protocol is efficient and can be used in other areas.